Preliminary studies of a canine 13C-aminopyrine demethylation blood test. - Moeller, E M (2001)
The objectives of this study were to determine whether a 13C-aminopyrine demethylation blood test is technically feasible in clinically healthy dogs, whether oral administration of 13C-aminopyrine causes a detectable increase in percent dose/min (PCD) of 13C administered as 13C-aminopyrine and recovered in gas extracted from blood, and whether gas extraction efficiency has an impact on PCD. A dose of 2 mg/kg body weight of 13C-aminopyrine dissolved in deionized water was administered orally to 6 clinically healthy dogs. Blood samples were taken from each dog 0, 30, 60, and 120 min after administration of the 13C-aminopyrine. Carbon dioxide was extracted from blood samples by addition of acid and analyzed by fractional mass spectrometry. None of the 6 dogs showed any side effects after 13C-aminopyrine administration. All 6 dogs showed a measurable increase of the PCD in gas samples extracted from blood samples at 30 min, 60 min, and 120 min after 13C-aminopyrine administration. Coefficients of variation between the triplicate samples were statistically significantly higher for the %CO2, a measure of extraction efficiency, than for PCD values (P < 0.0001). The 13C-aminopyrine demethylation blood test described here is technically feasible. Oral administration of 13C-aminopyrine did not lead to gross side effects in the 6 dogs. Clinically healthy dogs show a measurable increase of PCD in gas extracted from blood samples after oral administration of 13C-aminopyrine. Efficiency of CO2 extraction from blood samples does not have an impact on PCD determined from these blood samples. This test may prove useful to evaluate hepatic function in dogs.